2013
DOI: 10.1074/jbc.m113.489310
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Endoplasmic Reticulum Lipid Rafts Contributes to Lipotoxicity in Pancreatic β-Cells

Abstract: Background: Saturated fatty acids disrupt protein trafficking and promote endoplasmic reticulum (ER) stress in pancreatic ␤-cells. Results: Chronic palmitate selectively reduces ER sphingomyelin and cholesterol and disrupts ER lipid rafts. Conclusion: Altered ER lipid rafts contribute to defective ER protein export. Significance: This provides novel insights into the mechanisms of ␤-cell death that underlie type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 69 publications
2
91
0
3
Order By: Relevance
“…When palmitoylation was inhibited by 2-bromopalmitate, a nonmetabolizable form of palmitic acid, the induction of ER stress and the activation of caspase activity were attenuated in insulinoma cells and isolated islets (69), suggesting a role of protein palmitoylation, ceramide production, or fatty acid oxidation in SFA-induced ER stress. On the other hand, a lipidomic screen of palmitate-treated insulinoma cells found that altered sphingolipid metabolism may be implicated in the defective protein trafficking from ER to Golgi and disruption of ER lipid rafts, causing ER stress and subsequent  cell death (70)(71)(72). In addition, palmitate treatment of insulinoma cells impaired trafficking of ceramide from the ER to the Golgi apparatus, thus suppression of C/EBP (37) …”
Section: Er Stress and The Uprmentioning
confidence: 99%
“…When palmitoylation was inhibited by 2-bromopalmitate, a nonmetabolizable form of palmitic acid, the induction of ER stress and the activation of caspase activity were attenuated in insulinoma cells and isolated islets (69), suggesting a role of protein palmitoylation, ceramide production, or fatty acid oxidation in SFA-induced ER stress. On the other hand, a lipidomic screen of palmitate-treated insulinoma cells found that altered sphingolipid metabolism may be implicated in the defective protein trafficking from ER to Golgi and disruption of ER lipid rafts, causing ER stress and subsequent  cell death (70)(71)(72). In addition, palmitate treatment of insulinoma cells impaired trafficking of ceramide from the ER to the Golgi apparatus, thus suppression of C/EBP (37) …”
Section: Er Stress and The Uprmentioning
confidence: 99%
“…Previous lipidomic analyses have been performed predominantly on beta cells exposed to glucolipotoxic conditions [14]. The incorporation of high levels of palmitic acid (PA) into phospholipids was associated with beta cell damage [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest in cell-death response is the putative connection between plasma membrane rafts and mitochondria, as unveiled by the use of the raft-targeted drug edelfosine [37,141,157]. On these grounds, raft-like domains have been identified in the membranes of different subcellular organelles, such as mitochondria and endoplasmic reticulum, where their role remains largely elusive [37,[274][275][276][277]. These data, together with recent evidence showing distinct organelle interactions, particularly between endoplasmic reticulum and mitochondria [37,278,279], and that rafts or raft constituents can traffic to other subcellular organelles [37,157], suggest the existence of a raft-mediated dynamic network of communication between plasma membrane and different subcellular organelles that could modulate cell demise.…”
Section: Discussionmentioning
confidence: 99%